CERITA RAKYAT JONG DOBO DALAM MASYARAKAT SIKKA (KAJIAN LINGUISTIK KEBUDAYAAN) - Yoanita Dewi Roswita Kolo (Jurnal Lazuardi, 2022)
This research study about the folktale of JD in the society of Sikka was examined from the perspective of cultural linguistics. The purpose of this study was to know the form, function, and the meaning of folktale of JD in Sikka society. The results showed that the form of JD folktale of superstructure consists of the introduction, contents, and cover. JD folktale function can be divided into two parts, namely the function of manifest and latent functions. The manifest function consists of the referential function, conative function, and the poetical function while the latent functions of JD folktale are as means of entertainment and educational facilities. The meaning contained in the JD folktale is the didactic meaning, historical significance, economic meaning, and political meaning.didactic meaning, historical significance, economic meaning, and political meaning.